Cultural Variations in Lie Perception: A Semantic Prototype Study of Sulawesi's Ethnic Diversity - Ikhsan, Ikhsan (JELITA, 2024)
This study examines the cultural perception of deception among Indonesian ethnic groups, particularly in South and West Sulawesi. The data reveals two key findings; (1) factual inaccuracy ([+false]) serves as the primary criterion for lie identification, prioritizing objective truth over subjective intent, and (2) lie prototypicality is independent of the number of deceptive elements, with single-element [+false] statements rated as strongly deceptive. These results challenge classical lie prototype theories and highlight a distinct moral logic in collectivist contexts, where factual discordance may inherently undermine social trust. While offering novel insights, the study’s generalizability is limited by its focus on two Sulawesi communities and reliance on self-reported data. Future research should employ mixed-method approaches and expand to other Indonesian ethnicities to validate these patterns. By demonstrating how cultural norms reshape deception paradigms, this work advocates for pluralistic models of truth-assessment that move beyond Western-centric frameworks.